2021
DOI: 10.1111/acem.14279
|View full text |Cite
|
Sign up to set email alerts
|

Moving the needle on fall prevention: A Geriatric Emergency Care Applied Research (GEAR) Network scoping review and consensus statement

Abstract: Background: Although falls are common, costly, and often preventable, emergency department (ED)-initiated fall screening and prevention efforts are rare. The Geriatric Emergency Medicine Applied Research Falls core (GEAR-Falls) was created to identify existing research gaps and to prioritize future fall research foci.Methods: GEAR's 49 transdisciplinary stakeholders included patients, geriatricians, ED physicians, epidemiologists, health services researchers, and nursing scientists.We derived relevant clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 82 publications
2
15
0
Order By: Relevance
“…A recent consensus statement on geriatric fall prevention found multifactorial interventions to be most efficacious, focusing on medication review, exercise programs, and elimination of environmental hazards. 14 This supports the importance of geriatric EDs, where several dedicated specialists such as pharmacists, physical therapists, and case managers are available to evaluate patients as needed. 12 Also, a recent randomized control trial showed that an ED-initiated geriatric fall intervention reduced ED revisits by using pharmacists and physical therapists to assess patients prior to discharge.…”
Section: Discussionmentioning
confidence: 57%
“…A recent consensus statement on geriatric fall prevention found multifactorial interventions to be most efficacious, focusing on medication review, exercise programs, and elimination of environmental hazards. 14 This supports the importance of geriatric EDs, where several dedicated specialists such as pharmacists, physical therapists, and case managers are available to evaluate patients as needed. 12 Also, a recent randomized control trial showed that an ED-initiated geriatric fall intervention reduced ED revisits by using pharmacists and physical therapists to assess patients prior to discharge.…”
Section: Discussionmentioning
confidence: 57%
“…As an example, a falls history is often screened for as part of the ED nursing triage assessment 36 ; unfortunately, an ideal ED screening tool for falls history and risk does not currently exist, 43 but this is an area of active investigation. 21 Multiple scoring systems for frailty have been successfully used in the ED setting with good prediction of subsequent complications. 44 Notably, there is currently debate about the best frailty tool 45 and, similar to falls, selecting tools that are feasible and valid for the ED population is an active area of investigation.…”
Section: Considering the Importance Of Geriatric Syndromesmentioning
confidence: 99%
“…This includes the Geriatric Emergency Care Applied Research (GEAR) Network (R23 AG058926), 18 which is establishing research priorities, standardizing data approaches and measures for common geriatric emergency care conditions, developing and validating a data bank to support opportunities for investigators to conduct geriatric emergency care research, and facilitating future multicenter studies. This network has already been very successful 20–22 . Additionally, another collaborative NIH research infrastructure grant, GEAR 2.0‐Advancing Dementia Care (R61 AG069822), is focused on developing collaborative research to improve emergency care for persons living with Alzheimer’s disease and related dementias 23…”
Section: Previous Success Including Older Adults In Emergency Care Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…The original GEAR project (hereafter referred to simply as GEAR) is dedicated to improving ED care of the older adult and focused on the priority topics of: care transitions, cognitive impairment—delirium, medication safety, elder abuse and falls. Four of the five GEAR research priorities have already been published using this approach 13–16. GEAR 2.0 ADC is focused on optimising emergency care for PLWD and their care partners in the priority areas of: ED practices, ED care transitions, detection and communication and shared decision-making.…”
Section: Introductionmentioning
confidence: 99%